2007
DOI: 10.1111/j.1464-410x.2007.06791.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of preoperative diagnostics and location of lymph node metastases in presumed unilateral prostate cancer

Abstract: 564 men with impalpable or unilateral palpable prostate cancer and positive biopsy cores only in one prostate lobe had a radical prostatectomy (RP) combined with radioguided PLND and in some cases an extended PLND. RESULTSA median of six sentinel LNs (mean, seven) and six non-sentinel LNs (mean, seven) were dissected per patient; 52 of 564 men (9.2%) had positive LNs. Most men with unilateral disease had LN metastases on the same side of the pelvis. Comparing the clinical stage and grade with the tumour stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 26 publications
(30 reference statements)
2
27
1
7
Order By: Relevance
“…7,8 A study applying the sentinel lymphnode (LN) technique revealed a side-specific tropism of the metastatic dissemination in PCa and that unilateral prostate cancer preferentially metastasizes to ipsilateral pelvic LNs. 9 However, even if unilateral node dissection would reduce operating time, costs and morbidity, the dissection of sole LNs on the tumor-bearing side in men with unilateral PCa is not considered adequate. 10 Indeed, an assessment of the side of PCa based on biopsy results is not sufficiently accurate to evaluate the side of pathological PCa and the metastatic spread of PCa does not always follow a predictable pattern.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 A study applying the sentinel lymphnode (LN) technique revealed a side-specific tropism of the metastatic dissemination in PCa and that unilateral prostate cancer preferentially metastasizes to ipsilateral pelvic LNs. 9 However, even if unilateral node dissection would reduce operating time, costs and morbidity, the dissection of sole LNs on the tumor-bearing side in men with unilateral PCa is not considered adequate. 10 Indeed, an assessment of the side of PCa based on biopsy results is not sufficiently accurate to evaluate the side of pathological PCa and the metastatic spread of PCa does not always follow a predictable pattern.…”
Section: Introductionmentioning
confidence: 99%
“…By collecting more data on the tumor biology of unilateral disease, the critical aspects of this entity may be gradually unveiled. For instance, Weckermann and coworkers 45 investigated the data of 564 men with cT 1c or unilateral palpable disease with positive biopsy cores only in one lobe who underwent RP with some cases of pelvic node dissection. They found that unilateral PCa preferentially metastasized to the ipsilateral pelvic lymph nodes.…”
Section: Current Protocols Of Focal Cryoablationmentioning
confidence: 99%
“…Furthermore, because a proportion of PCas now being diagnosed are unifocal, unilateral, or of lower malignant potential (''clinically insignificant''), this has raised questions as to whether all patients need radical treatment. [1][2][3][4][5][6] According to CaPSURE data, the proportion of patients with favorable or low-risk tumor characteristics has risen from 29.8% in 1989 to1992 to 45.3% in 1999 to 2001. Moreover, this tendency is being accelerated today with the implementation of extended and multicore prostate biopsy.…”
mentioning
confidence: 99%
“…1a). [23][24][25][26][27][28][29][30][31] The main advantage of this technique is that the images are generated easily and quickly, and give a direct overview over the radioactive hotspots. A disadvantage is that SN located near the site of injection can become obscured by the radioactive signal coming from the injection site.…”
Section: Lymphoscintigraphymentioning
confidence: 99%
“…Although, unilateral PCa tend to metastasize the ipsilateral side, bilateral PLND should be recommended. 30 Some studies reported the laparoscopic SN biopsy as a staging procedure before radiotherapy. These studies demonstrated that the SN procedure is a reliable tool for staging with high accuracy and minimal complications when comparing the ePLND.…”
Section: Clinical Implications Of Sn Biopsy For Pcamentioning
confidence: 99%